ELECTROLYTE DESIGN FOR QUASI-SOLID-STATE LITHIUM-SULFUR BATTERIES - Aliyakbarova, Marzhan (Nazarbayev University School of Engineering and Digital Sciences, 2025)
This study investigates the creation and characterization of quasi-solid-state electrolytes (QSSEs) for lithium-sulfur batteries (LSBs), with a focus on improving ionic conductivity. The research started conducting literature review with a highlight of QSSE preparation techniques. For the creation of polymer electrolytes (PEs) based on polyvinylidene fluoride-co-hexafluoropropylene (PVDF-HFP) and lithium bis(trifluoromethylsulphonyl)imide (LiTFSI), the study optimizes the LITFSI content. Moreover, this study compares three widely used preparation methods, including electrospinning, solution casting, and spin coating. The scanning electron microscopy coupled with energy dispersive X-ray spectroscopy (SEM-EDS), Fourier-transform infrared spectroscopy (FTIR), X-ray diffraction (XRD), potentiostatic electrochemical impedance spectroscopy (PEIS) and thermal stability analyses were done to investigate morphology, composition, ionic conductivity, and thermal characteristics of the produced electrolytes. According to XRD analysis shows that preparation method affects the crystallinity of the resulting PE. Concurrently FTIR shows modest crystallinity and strong ion-polymer interaction of electrospun sample, which makes electrospinning technique more favorable for efficient ion transport in PEs. Moreover, the PEIS analysis confirms that electrospinning greatly enhances the PE's ionic conductivity.
Keywords: lithium-sulfur batteries; solid state electrolytes; electrospinning; type of access: open access